(untitled) (Archives of Mechanics - Test, 2002)
The aim of the paper is to study the description of plastic strain in metals produced by a hierarchy of plastic slip and shear banding processes: from slip lamellae and slip bands to coarse slip bands, which may further transform into transgranular micro-shear bands and form clusters of micro-shear bands. Constitutive description accounting for the contribution of shear banding was proposed and possible simplifications are discussed from the point of view of applications for numerical simulation of metal shaping operations.